2019
DOI: 10.3892/ijmm.2019.4187
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ZEB1-AS1 promotes migration and metastasis of bladder cancer cells by post-transcriptional activation of ZEB1

Abstract: The prognosis for patients with metastatic bladder cancer (BCa) is poor, and has not been improved by current treatment methods. Long noncoding RNAs (lncRNAs) are involved in the pathology of various tumors, including bladder cancer. However, the role of zinc finger E-box-binding homeobox 1-antisense 1 (ZEB1-AS1) in BCa progression and metastasis remains unclear. The present study determined the expression level of ZEB1-AS1 in BCa and additionally investigated the functional role of ZEB1-AS1 in BCa metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…LncRNAs are recognized as a class of long noncoding RNAs approximately more than 200 nucleotides, which are closely associated with occurrences of cancers . A growing number of evidence has demonstrated that lncRNAs, such as ZEB1‐AS1, PEG10, and UCA1, play important regulatory roles in the proliferation, migration, and invasion of BC . Based on our preliminary lncRNA microarrays, lncRNA muscleblind‐like 1 antisense RNA 1 (MBNL1‐AS1) level in bladder tumor tissues is decreased by 99.2 times than that in adjacent nontumor tissues.…”
Section: Introductionmentioning
confidence: 91%
“…LncRNAs are recognized as a class of long noncoding RNAs approximately more than 200 nucleotides, which are closely associated with occurrences of cancers . A growing number of evidence has demonstrated that lncRNAs, such as ZEB1‐AS1, PEG10, and UCA1, play important regulatory roles in the proliferation, migration, and invasion of BC . Based on our preliminary lncRNA microarrays, lncRNA muscleblind‐like 1 antisense RNA 1 (MBNL1‐AS1) level in bladder tumor tissues is decreased by 99.2 times than that in adjacent nontumor tissues.…”
Section: Introductionmentioning
confidence: 91%
“…lncRNA zinc finger E-box binding homeobox 1 antisense 1 (ZEB1-AS1) is considered an oncogene in diverse tumors (14). ZEB1-AS1 facilitated cell migration and metastasis via targeting heterogeneous nuclear ribonucleoprotein D0 (AUF1) to activate ZEB1 expression in bladder cancer (15). Another study hinted that ZEB1-AS1 played an anti-fibrotic role in diabetic nephropathy (16).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs regulate gene expression in multiple ways including transcription, posttranscription, and epigenetic mechanism 27‐29 . Most lncRNAs were found in the nucleus.…”
Section: Discussionmentioning
confidence: 99%